2012
DOI: 10.1100/2012/938138
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Biotechnology of Follicle Development

Abstract: Growth and development of ovarian follicles require a series of coordinated events that induce morphological and functional changes within the follicle, leading to cell differentiation and oocyte development. The preantral early antral follicle transition is the stage of follicular development during which gonadotropin dependence is obtained and the progression into growing or atresia of the follicle is made. Follicular growth during this period is tightly regulated by oocyte-granulosatheca cell interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(95 citation statements)
references
References 94 publications
1
88
0
6
Order By: Relevance
“…(Johnson and Woods, 2009;Palma et al, 2012). The results of the present study confirmed the complexity of this process, as 160 genes were identified, associated with various GO-terms, such as extracellular region, proteinaceous extracellular matrix, intermediate filament organization, peptidase activity, and endopeptidase activity.…”
Section: Discussionsupporting
confidence: 89%
“…(Johnson and Woods, 2009;Palma et al, 2012). The results of the present study confirmed the complexity of this process, as 160 genes were identified, associated with various GO-terms, such as extracellular region, proteinaceous extracellular matrix, intermediate filament organization, peptidase activity, and endopeptidase activity.…”
Section: Discussionsupporting
confidence: 89%
“…Follicular growth involves several steps, including the primordial to primary follicle transition, recruitment of theca cells, formation of follicular antrum, and differentiation of cumulus cells [1,2]. Previous reports clarified that the mechanism through which follicular growth is regulated involves the interaction between oocytes and the surrounding granulosa, theca, and stromal cells in the ovary [1][2][3][4]. However, these studies were based on the culture of isolated follicles or on histological methods.…”
Section: Introductionmentioning
confidence: 96%
“…Histological evaluation has been used to determine the features of preantral follicle population, classification, stages of development, and morphology, as well as follicular density [12]. However, this methodology is time consuming and requires the development of technical approaches to overcome this problem [13].…”
Section: Introductionmentioning
confidence: 99%